POSTGLACIAL INDUCED SURFACE MOTION AND GRAVITY IN LAURENTIA FOR UNIFORM MANTLE WITH POWER-LAW RHEOLOGY AND AMBIENT TECTONIC STRESS - Wu P. (My University, 2001)
Previous investigations of postglacial sea levels around Laurentia in a non-linear earth without ambient stress found that non-linear uniform mantle models cannot explain the relative sea level data around the ice margin. In this study, a 3D finite element model of postglacial readjustment is used to calculate the Earth's response due to realistic ice and eustatic water loads on stratified mantle with non-linear rheology and ambient tectonic shear stress. By varying the creep parameter A* and the ambient stress level in a uniform mantle, it is found that the combination A* around 3x10-35 Pa-3 s-1 and ambient stress level around 10 MPa is able to explain the sea level data both outside and inside the Laurentian ice margin - although for certain sites inside, a slightly thicker ice is required to improve the fit to the data. Other geophysical and geodetic observables - namely uplift rate, horizontal velocity, free air gravity and the rate of change of gravity - have also been calculated for this model.
Keywords: HOLOCENE; SEA-LEVEL CHANGES; UPLIFT RATE; HORIZONTAL VELOCITY; GRAVITY; LAURENTIA; RHEOLOGY; TECTONICS; STRESS; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен